AN OVERVIEW OF ECOFEMINISM: WOMEN, NATURE AND HIERARCHIES - Yıldız Merve ÖZTÜRK (Fırat University, 2020)
Ecofeminism is an interdisciplinary critical theory which claims that environmental and women's issues are interconnected because of the objectification of women and nature in a male-dominant society. According to this theory, the system forms a male-centred hierarchy and dualities, creating inequality in society and providing the superiority for men. On the other hand, the hierarchy and dualities are used to exert pressure on non-male beings and marginalize them. Thus, in the male-dominant hierarchical order dualities such as male/female, culture/nature, human/nature, white/black, unconscious/unconscious, logic/emotion, soul/body occur, and former dominates the latter. That is, in this order, man is superior to woman, culture is superior to nature, and logic is to emotion. Also, since the man is considered superior to the woman, all the superior features are attributed to the male and the inferior features are associated with the female. In this way, while man symbolizes culture, consciousness, logic and spirit, woman represents nature, unconsciousness, emotion and body. In this case, women and nature become close to each other in a male-dominant society and are similarly conceptualized. The main factor causing this bond is the ability of both nature and women to reproduce and create. For example, while women bring humans into the world, nature ensures the continuity of life on earth with natural resources. Another factor is that both of them have a passive role in society and are dependent. Women are pushed to live a domestic life and become passive due to their fertility. Women who cannot achieve their economic freedom become dependent on men. On the other hand, nature is not an active being intrinsically. Since nature cannot move and speak, it has a position that is dependent on humans. The bond between woman and nature naturalizes the fertility of women and feminizes the fruitfulness of nature. For example, the fact that the woman is closer to nature ensures that her reproducibility is perceived as a natural condition, and motherhood is portrayed as the woman's most natural duty. Besides, it is natural for women to be domestic because of their biological structure. Thus, the fact that women cannot acquire social identity and depend on men is normalied, and women exist as objects in society. On the other hand, nature stands out in the male-centred system with its productivity and generosity, just like a mother. Nature serves the patriarchal system with its renewable resources. Thus, the system perceives nature as an object that provides abundance, infinite resources and power. As a result, both women and nature are objectified and exploited in the masculine-dominated society. The system puts forward women's closeness with nature to exclude them from society. This study sheds light on how the male-centred hierarchy and dualities crush non-male beings while glorifying men; explains why nature and women are perceived closer to each other. The st